Forming protective alumina scale for ductile refractory high-entropy alloys via aluminizing. (August 2020) - Sheikh, Saad; Gan, Lu; Montero, Xabier; Murakami, Hideyuki; Guo, Sheng
Abstract: Refractory high-entropy alloys (RHEAs), or multi-principal-element refractory alloys, have been intensively studied in recent years, due to their attractive potential for ultrahigh-temperature structural applications. One formidable challenge facing the materials development for RHEAs though, is to simultaneously achieve good oxidation resistance and good mechanical properties, which unfortunately often impose contradictory microstructural requirements. So far, there exist no ductile RHEAs that possess reasonable oxidation resistance, and the formation of protective oxide scales such as alumina in them is never seen. Here we report, for the first time, a strategy to form protective alumina scale in ductile RHEAs upon high temperature exposure, using a tailor-designed two-step pack aluminizing process. Very importantly, the oxidation resistance of ductile RHEAs improves tremendously, as evidenced from harsh cyclic oxidation tests, thus providing a huge impetus to push forward the further development of RHEAs, towards ultrahigh-temperature applications. Highlights: a two-step pack aluminizing process forms protective alumina scale in ductile RHEAs. a TiAl3 /TiAl/Ti2 AlNb and substrate multi-layered gradient structure is achieved. Crack-free TiAl3 coating forms on the top surface of Al0.5 Cr0.25 Nb0.5 Ta0.5 Ti1.5 The oxidation resistance of ductile RHEAs improves tremendously after aluminizing.